2010
DOI: 10.1182/blood-2010-03-273151
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of eliglustat tartrate (Genz-112638), an oral substrate reduction therapy for Gaucher disease type 1

Abstract: Eliglustat tartrate (Genz-112638), a specific inhibitor of glucosylceramide synthase, is under development as an oral substrate reduction therapy for Gaucher disease type 1 (GD1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 20 publications
(29 reference statements)
2
123
0
1
Order By: Relevance
“…(36) Eliglustat, a more potent and specific inhibitor of glucosylceramide synthase that is currently in clinical trials for GD1, was reported to increase lumbar spine bone mineral density after 1 and 2 years of treatment, with major gains in DXA scores in osteopenic and osteoporotic patients. (37,38) The signature complication of GD1 in the skeleton is the occurrence of AVN, which is clinically devastating when it involves the cortical bone. As with fractures, we did not find any association of AVN with the severity of visceral disease or with biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…(36) Eliglustat, a more potent and specific inhibitor of glucosylceramide synthase that is currently in clinical trials for GD1, was reported to increase lumbar spine bone mineral density after 1 and 2 years of treatment, with major gains in DXA scores in osteopenic and osteoporotic patients. (37,38) The signature complication of GD1 in the skeleton is the occurrence of AVN, which is clinically devastating when it involves the cortical bone. As with fractures, we did not find any association of AVN with the severity of visceral disease or with biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…␤ -glucocerebrosidase as evidenced by reversal of spleen and liver enlargement, correction of anemia, and improvements in thrombocytopenia and bone density ( 6 ). Phase 3 trials with eliglustat tartrate are currently in progress.…”
Section: Gcs Activitymentioning
confidence: 99%
“…2 We recently reported the pharmacokinetics and maximum tolerated doses of eliglustat tartrate from phase 1 studies in healthy normal subjects 3 as well as promising results from the 1-year primary analysis period of a phase 2 trial in GD1 patients. 4 Here we present longer-term efficacy and safety data obtained after 2 years of treatment in the phase 2 study and assess patient responses to eliglustat tartrate with reference to evidence-based therapeutic goals established for intravenous enzyme replacement therapy (ERT) with imiglucerase. 5 …”
Section: Introductionmentioning
confidence: 99%